Ill-gotten Money and the Economy : Experiences from Malawi and Namibia - Yikona, Stuart (World Bank, 2012)
Over the last 20 years, the international community has significantly stepped up its efforts to prevent, detect, and deter money flows related to criminal activities and terrorism financing. Since the early 2000s, this drive has extended to developing countries, with most of them introducing anti-money laundering (AML) policies. The primary driver behind this is law enforcement; these policies are aimed at detecting and tracing flows of ill-gotten money, which would enable authorities to fight and prevent crime and recover assets of crime, corruption, and tax evasion. The core objective of this study is to introduce economics into the international debate about anti-money laundering, and to introduce the idea of the usefulness and effectiveness of such policies. The study focuses on two developing countries: Malawi, a low-income country, and Namibia, a middle-income country. The findings presented in this study are based on an extensive literature research; World Bank discussions with numerous public- and private-sector officials and representatives of the Governments of Malawi and Namibia during a Bank mission in November 2010; and workshops conducted in both countries in February 2011 to obtain feedback on the preliminary findings. In conducting this study, the team adopted an interactive approach. This was critical because mobilization of local expertise is essential not only in establishing a complete picture of current and future AML challenges, but also in designing policy considerations that subsequently are widely supported.